1996
DOI: 10.2165/00007256-199621040-00004
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Acute and Chronic Exercise on Sleep

Abstract: Studies attempting to ascertain the effects of acute and chronic exercise on measures of sleep have yielded conflicting results and interpretations. Methodological differences among studies may explain this lack of consensus; however, small sample sizes and subsequently low statistical power may also have contributed. In an attempt to resolve these issues, this review used meta-analytical techniques to: (a) re-examine the effects of exercise on sleep; and (b) examine possible moderators of these effects. Studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
136
3
15

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 240 publications
(171 citation statements)
references
References 58 publications
5
136
3
15
Order By: Relevance
“…Improvements in subjective sleep data were reported in both groups, with the difference being statistically significant in the running group. In contrast to the expected increase in SWS and reduction of REM sleep following acute or chronic exercise [103], a more recent study found no changes in SWS and increased REM sleep following a three month exercise intervention on obese adolescents [127]. In their study, Mendelson and colleagues reported that a 12-week exercise program (between 160 and 180 min per week) consisting of aerobic and resistance training, was effective in improving total sleep time by reducing time awake after sleep onset, without affecting sleep stage characteristics.…”
Section: Effects Of Exercise On Sleepmentioning
confidence: 63%
See 2 more Smart Citations
“…Improvements in subjective sleep data were reported in both groups, with the difference being statistically significant in the running group. In contrast to the expected increase in SWS and reduction of REM sleep following acute or chronic exercise [103], a more recent study found no changes in SWS and increased REM sleep following a three month exercise intervention on obese adolescents [127]. In their study, Mendelson and colleagues reported that a 12-week exercise program (between 160 and 180 min per week) consisting of aerobic and resistance training, was effective in improving total sleep time by reducing time awake after sleep onset, without affecting sleep stage characteristics.…”
Section: Effects Of Exercise On Sleepmentioning
confidence: 63%
“…Additionally, several studies account that partaking in regular physical activity is associated with a reduced risk of sleep disturbances and better sleep quality in adults [101]. The body of evidence suggests that vigorous exercise increases total sleep times by reducing sleep onset latency (SOL) and waketime after sleep onset (WASO) [18,102,103]. Separately, chronobiological research shows that exercise can facilitate a phase advance in daily circadian entrainment in adult populations [104,105] due to its role as a non-photic time cue [106].…”
Section: Effects Of Exercise On Sleepmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms by which exercise may improve sleep quality require further study. There is some evidence to suggest physiologic pathways including muscular relaxation, decreases in sympathetic tone, or thermal changes induced by exercise may promote sleep (47)(48)(49). Exercise has also been associated with improvements in depressed mood and anxiety levels (50 -52) that influence sleep quality.…”
Section: Discussionmentioning
confidence: 99%
“…In those who reported insomnia or hypersomnia greater than 40% had a psychiatric disorder. Physical activity is shown to improve sleep duration and quality of sleep (Kubitz, Landers, Petruzzello & Han, 1996;Driver 2000). Regardless of the type of PA that individuals engaged in REM sleep was longer in duration.…”
Section: Psychological and Physiological Response To Stressorsmentioning
confidence: 99%